A geografia no currículo do ensino médio e no vestibular da UFRN: 2001-2007 - Ferreira, Hilma de Azevedo (2008)
This work examines the results of the selecting process to enter Universidade Federal do Rio Grande do Norte called Vestibular, in 2001, 2003, 2005 and 2007, in relation to the necessary knowledge presented by the candidates in the Geography area. It observes the contents in the discursive exams and its corresponding results discussing them from the official curriculum of the Secondary School, as it is stated in the official documents of Ministério da Educação(MEC): Parâmetros Curriculares Nacionais do Ensino Médio (PCNEM), Orientações Curriculares Nacionais para o Ensino Médio (OCNEM) e Orientações Educacionais Complementares aos Parâmetros Curriculares Nacionais (PCN+ do Ensino Médio). We aim to highlight what are the contents and background of the Geography curriculum according to the orientations of the official curriculum; discuss in what measure these contents are present in the questions and in the correct answers of the candidates as well as reflect upon what possibly is suggested by those results concerning the knowledge presented in the answers. In this investigation process, the history of the teaching in Brazil is taken up together with the statistical data about the Fundamental School and about Higher Education in the last years. Both map the scenario in which this research takes place as well as make knowledgeable some variables such as: cultural, economical, political and social structures. The discussion takes place between the curriculum and the teaching, Geography teaching and Secondary School in Brazil articulating these variables with the question of accessibility to Higher Education through the Vestibular . Despite the limitations of this research in terms of methodology and deepening of analysis, the results led us to important observations which can contribute to the understanding of that the students´ performance in the Geography examination has several outspreads. These must be thought with scientific exactness in order to avoid any rushed and careless explanations leading to conclusions that may have serious consequences for the teaching systems and the students